2017
DOI: 10.1097/md.0000000000008058
|View full text |Cite
|
Sign up to set email alerts
|

The atherogenic index of plasma is a strong and independent predictor for coronary artery disease in the Chinese Han population

Abstract: Dyslipidemia is one of the most important factors for coronary artery disease (CAD). The atherogenic index of plasma (AIP), a new comprehensive lipid index, might be a strong marker for predicting the risk of CAD.A hospital-based case–control study including 2936 CAD patients and 2451 controls was conducted in a Chinese population. Traditional lipid parameters were detected, and nontraditional lipid comprehensive indexes were calculated.Compared with controls, CAD patients had higher levels of total cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
214
2
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(237 citation statements)
references
References 22 publications
14
214
2
7
Order By: Relevance
“…These data indicated that IL-8 level is affected by intensity of exercise. The present study detected significant increase in atherogenic index in both obese non-ovx and obese ovx subgroup versus lean subgroup, these results also comes in agreement with other several studies, As Pourfarzam, et al [63] ; Zhan et al [64] ; Gaojun Cai et al [65] ; Shen et al [66] demonstrated that atherogenic index associated with metabolic syndrome and it was higher in coronary heart diseases. Furthermore it was positively correlated with TC, TG and negatively correlated with HDL-C.…”
Section: Discussionsupporting
confidence: 93%
“…These data indicated that IL-8 level is affected by intensity of exercise. The present study detected significant increase in atherogenic index in both obese non-ovx and obese ovx subgroup versus lean subgroup, these results also comes in agreement with other several studies, As Pourfarzam, et al [63] ; Zhan et al [64] ; Gaojun Cai et al [65] ; Shen et al [66] demonstrated that atherogenic index associated with metabolic syndrome and it was higher in coronary heart diseases. Furthermore it was positively correlated with TC, TG and negatively correlated with HDL-C.…”
Section: Discussionsupporting
confidence: 93%
“…AIP was found to be higher in 2936 patients with coronary artery disease versus 2451 controls [25], while AIP has also been suggested as an independent risk factor for coronary artery disease [24,25]. An AIP value below 0.11 has been associated with low, values from 0.11 to 0.24 with intermediate, and values exceeding 0.24 with high cardiovascular disease risk [20][21][22]24,57]. Dobi a sov a et al examined 1433 subjects with various risks of atherosclerosis and reported that AIP directly correlated with the fractional esterification rate of HDL (r ¼ 0.803), and inversely correlated with LDL particle size (r = À0.776).…”
Section: Discussionmentioning
confidence: 94%
“…AIP reflects the lipoprotein composition in plasma, and it has been postulated as a surrogate marker for small dense LDL particles, and also as a predictor of atherosclerosis, cardiovascular risk, and even effectiveness of therapy [18][19][20][21]25,27]. AIP was found to be higher in 2936 patients with coronary artery disease versus 2451 controls [25], while AIP has also been suggested as an independent risk factor for coronary artery disease [24,25]. An AIP value below 0.11 has been associated with low, values from 0.11 to 0.24 with intermediate, and values exceeding 0.24 with high cardiovascular disease risk [20][21][22]24,57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TC/HDL-C and TG/HDL-C molar ratios are associated with coronary heart disease (24). Furthermore, the atherogenic index is used as a predictor of atherosclerosis and coronary artery disease (25,26). The increase in cholesterol is associated with the risk of fatty liver and atherosclerosis (5).…”
Section: Discussionmentioning
confidence: 99%